Pengaruh Organizational Citizenship Behavior, Employee Engagement, Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PDAM Kota Malang - Dewi Irawati; Hadi Sunaryo; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine how the influence of Organizational Citizenship Behavior, Employee Engagement, and Organizational Culture on Performance at PDAM Malang City. This type of research uses a quantitative approach. The data analysis technique used in this research is multiple linear regression. From the results of this study, the following results were obtained: the independent variable that was most appreciated was the organizational culture variable because it had the highest average value, simultaneously the variables Organizational Citizenship Behavior, Employee Engagement, and Organizational Culture had a significant positive effect on performance, Organizational Citizenship Behavior had a significant positive effect on performance. significant positive on performance, employee engagement variable has a significant positive effect on performance, organizational culture variable has a significant positive effect on performance. Keywords: Organizational Citizenship Behavior, Employee Engagement, Organizational Culture, Performance.